The Defence Mechanism on Malignant Disease - Hunter, R D (Res Medica, 2014)
From a dissertation read before the Society on November 6th, 1968. The original suggestion implicating immunological factors in the natural history of malignant disease has been ascribed to Paul Ehrlich (1). Confirmation of this concept has waited fifty years for developments in knowledge and technique but its application allows not only some understanding of observed phenomena, but speculation on a rational approach to treatment and on a scientific establishment of the aetiological factors involved. Traditional teaching defines this group of conditions by the type of tissue change involved, the degree of differentiation and extent of spread. From these a prognosis is assessed and the clinical picture tends to be one of steady progression, interrupted by therapeutic endeavour, but culminating in the death of the patient. Variations on this picture are seen in clinical practice.